Influência das condições térmicas e qualidade do ar em salas de aula no desempenho cognitivo de estudantes universitários - Storopoli, João Henrique (2017)
The cognitive performance analysis is key to stablishing strategies and pedagogical teaching tools in any academic level. However, classroom´s internal environmental factors, such as: ventilation, room temperature, humidity, CO2 levels, among others, can present significant influence on student´s cognitive performance. Thus, this research had as objective to study the relation between internal environmental factors and the student´s cognitive performance. For this purpose, the methodologic approach adopted in this research was composed by gathering data from two different tests, made to measure the cognitive performance of a university student group. The tests were applied in a previously selected class room, in which the CO2 levels humidity, air speed and room temperature were measured during the time that the students remained in the class room. On an effort to verify the cognitive performance variation of the students by the class room internal environmental condition, tests were applied em three successive days with the classrooms prepared in the following set up´s: i) Air-Conditioning on windows and door closed; ii) Air-Conditioning off windows and door opened and, iii) Air-Conditioning off windows and door closed. The internal environmental conditions have influenced the environmental perception and the student´s cognitive performance. The classroom setup affects the internal environmental conditions. There is positive correlation between temperature and humidity, therefore, it is imperative to use crossed ventilation in order to improve the internal classroom´s conditions. The cognitive performance´s variation and angular coefficient were bigger when the conditions were better. Therefore, environmental quality and thermic discomfort reduce the student´s performance. The research can contribute towards the awareness of this problem by the Educational Institutions, in order to adopt measures to optimize environmental conditions inside classrooms.